Experimental and theoretical studies on vanadium bromoperoxidase activity of alkyne arm dioxidovanadium(V) complex: Crystal structure, spectral studies, and DFT calculations. (1st May 2018) - Neelakantan, M.A.; Balakrishnan, Chithiraivel; Kowsalya, P.; Selvarani, V.
Graphical abstract: Dioxidovanadium(V) complex was synthesized and structurally characterized. Non covalent interactions in the complex and vanadium dependent bromoperoxidase activity was studied. Abstract: The alkyne arm bearing dioxidovanadium(V) complex was synthesized by the reaction of vanadium sulphate, 1-[2-hydroxy-4-(prop-2-yn-1-yloxy)phenyl]ethanone and propane-1, 2-diamine. The synthesized complex was characterized by various spectral techniques and its structure was determined using single-crystal X-ray diffraction analysis. Vanadium centre has square-pyramidal based geometry with an axial oxido ligand and the equatorial positions are occupied by another oxido ligand and phenolato oxygen, imine nitrogen and free amine nitrogen atoms. DFT and TD-DFT calculations were examined to identify the electronic structure, and electronic transitions of the complex observed in the absorption spectra. The percentage of intermolecular interactions in the crystal structure has been evaluated by 3D Hirshfeld surfaces and 2D fingerprint plots. The CH⋯π and intermolecular interactions of the complex were examined using Bader's theory of QTAIM by ADF 2017. The dioxidovanadium(V) complex mimics as an efficient vanadium-dependent bromoperoxidase towards the bromination of phenol red in acetonitrile medium at room temperature.